Awareness on prostate cancer and screening practices among men attending outpatient at a referral hospital in Kigali, Rwanda: A quantitative study. (2020) - Benurugo, Genevieve; Munyambaraga, Emile; Chironda, Geldine; Bisanukuri, Evergiste
Abstract: Background: Prostate cancer is estimated to be the second of all under diagnosed cancer and it is ranged the sixth among the cause of cancer mortality worldwide. The sensitization related to prostate cancer awareness and its screening needs to be encouraged among adult men to avoid late consultation and reduce prostate cancer morbidity and mortality. Purpose of the study: To assess prostate cancer awareness and screening practices among adult males attending outpatient department at Kigali university teaching hospital, Rwanda. Methodology: A quantitative, descriptive cross-sectional design was used in this study. A systematic random sampling technique was used to select 257 adult males, who participated in the study. Participants were chosen from among the men who consulted urology and general surgery services at University Teaching hospital of Kigali (CHUK) Rwanda, during 8 weeks of the study period. Results: Among 257 participants in the study, the great proportion (43%) of respondents ranged between 51 and 60. 80% of the respondents were aware of prostate cancer existence and reported the health provider as being the major source of the information. Knowledge on various domains was low and 64% of the respondents were not aware of the risk factors of prostate cancer, 32% did not know the prevention measures of prostate cancer, 64% of the respondents were aware of prostate cancer screening using PSA exam and 49% of the respondents had undergone screening by performing PSA exam. Overall prostate cancer awareness and screening practice was 75% and 49.5% respectively. Having a university level education was significantly associated with P Ca awareness and screening practices (p < 0.004), and working in public institutions had a strong correlation to Prostate cancer awareness and screening practice (p < 0.000). Conclusion: The level of awareness of prostate cancer was high while knowledge on some areas was low. Screening practices were found to be poor, almost half of participants did not perform PSA test. There is a need to improve health education to the community regarding prostate cancer to enhance knowledge and increase the rate of screening.